IMPROVING THE ABILITY TO WRITE REVIE TEXTS THROUGH LEARNING MODELS COOPERATIVE INTEGRATED READING AND COMPOSITIO (CIRC) CLASS XI STUDENTS STATE SENIOR HIGH SCHOOL 1 SARADAN (International Journal of Education and Literature, 2023)
One of the goals of learning Indonesian is that students can write. Writing is an activity of expressing ideas that are in the mind which are obtained through reading, speaking, and listening activities which are described in a word to become a sentence. One of the abilities that students must have in learning Indonesian is writing review texts. The review text is one of the texts that is learned in class XI at the senior high school level. Writing review texts has not obtained optimal results following the minimum school completeness criteria. So we need a learning model that can facilitate students, namely the cooperative integrated reading and composition (CIRC) learning model. The purpose of this study was to obtain results of improving the ability to write review texts through the cooperative integrated reading and composition (CIRC) learning model. SMAN 1 Saradan became the research location. As many as 28 students in class XI MIPA 3 in the 2022/2023 school year were the subjects of the study. Classroom Action Research (PTK) is a research design that goes through four research steps namely planning (plan), action (action), observation (observation), and reflection through two cycles. Tests and observations become instruments in research. Data analysis was carried out through a qualitative approach by calculating the class average value using the percentage of classical completeness. Students who get a KKM score of ≥75 are declared complete. The results of the study were that the ability to write review texts without going through cooperative integrated reading and composition (CIRC) at SMAN 1 Saradan was 82.2, meaning that there were 23 whose grades did not exceed the KKM. While the results of the study were able to write review texts through cooperative reading and composition (CIRC) in cycle I 67.9% or 19 students in the less category. Whereas after being given cycle II it showed a result of 3.6% or 1 student in the less category. Based on the results of the study it was concluded that students' ability to write review texts through cooperative integrated reading and composition (CIRC) can be increased.